Pengaruh Kualitas Produk, Kualitas Pelayanan dan Promosi Terhadap Keputusan Nasabah Menggunakan Pembiayaan Murabahah dengan Religuisitas sebagai Variabel Moderating (Studi pada BMT Bina Insan Sejahtera Kota Jambi) - Putri, Bella Hermanika; Majid, M Nazori; Nengsih, Titin Agustin (Universitas Batanghari Jambi, 2024)
This quantitative study uses religion as a moderating variable to investigate how customer decisions are impacted by factors related to promotion, product quality, and service quality. The purpose of this research is to determine whether factors have an affect on one another. Utilizing a questionnaire approach, the study was conducted in Jambi City at BMT Bina Insan Sejahtera. The Saturated Sampling Technique was utilized to gather samples from 88 respondents for this study. The research's hypotheses are that: (1) customer decisions are significantly influenced by the quality of the product; (2) customer decisions are significantly influenced by the quality of the service; (3) customer decisions are significantly influenced by promotion; and (4) customer decisions are significantly influenced by religion (The following are the ways in which religiosity influences customer decisions: (5) it strengthens or weakens the influence of product quality; (6) it strengthens or weakens the influence of service quality; and (7) it moderates the influence of promotion quality. The research yielded the following conclusions: (1) customer decisions are significantly influenced by product quality; (2) customer decisions are influenced by service quality; (3) customer decisions are influenced by promotion; (4) customer decisions are influenced by religiosity; (5) religiosity increases the influence of product quality on customer decisions; and (6) religiosity decreases the influence of service quality on customer decisions. (7) Religiosity reduces the impact of advertisements on purchasing decisions.